NCMP-23. FACIAL PALSY INDUCED BY CANCER IMMUNOTHERAPY: A SINGLE CENTER RETROSPECTIVE STUDY. (5th November 2018) - Yuen, Carlen; Reid, Pankti; Soliven, Betty; Zhang, Zuoli; Luke, Jason; Rezania, Kourosh
Abstract: Monoclonal antibodies to Cytotoxic T-lymphocyteassociated antigen 4 (CTLA-4) [ipilimumab] and programmed cell death (PD1) receptor or ligand (PDL1) [pembrolizumab, nivolumab, atezolizumab] are increasingly used for the treatment of metastatic cancer. The augmented immune response enabled by these agents leads to the emergence of a class of side effects called immune-related adverse effects (irAEs) manifesting as autoimmune-like diseases. Neuromuscular complications such as polyneuritis, Guillain Barré syndrome (GBS)and myasthenia gravis are the most common; facial paralysis is only rarely reported. In this retrospective study, we reviewed the records of 364 patients who underwent immunotherapy in our center, for facial paralysis and Bells palsy, and identified five patients: 4 males and 1 female, ages 39 to 68 (average 55 years old) at the time of occurrence of facial paresis. Four patients had metastatic melanoma, all were treated with ipilimumab, in combination with nivolumab or pembrolizumab in 3 and 1 patients, respectively; the remaining patient had metastatic bladder and was treated with atezolizumab. Facial paralysis occurred within 1–23 weeks after starting immunotherapy and was unilateral in four patients. One patient had a multifocal neuropathy affecting limb and multiple cranial (including right facial) nerves; unilateral facial paresis emerged during the course of a GBS like condition in another patient. Lymphocytic pleocytosis was seen in CSF of three patients who had a lumbar puncture, MRI showed enhancement of the intracranial portion of the affected facial nerve in 4 patients. All but one patient, who had concomitant herpes labialis, were treated with steroids, with complete or significant improvement in 4; in the 5th patient facial weakness was still present after 3 months, before being lost to follow up. CONCLUSION: Facial paralysis is a less frequent neurological irAE, 1.4% in our cohort, and usually has a good prognosis.